The potential of dynamic controlled atmospheres and possible mechanisms in mitigating superficial scald in Apples cv. ‘Granny Smith’ - Mditshwa, Asanda (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhDAgric)--Stellenbosch University, 2015.